Towards Immersive Learning in Object-Oriented Paradigm: A Preliminary Study - Fernandes, Filipe; Werner, Claudia (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2019: Anais do XXI Simpósio de Realidade Virtual e Aumentada, 2019)
Object-Oriented Paradigm Teaching is mandatory in the curriculum of the courses of the Computing area. Students are taught fundamental concepts about this paradigm, such as class, object, encapsulation, polymorphism, generalization and composition. One of the major challenges of Software Engineering is to teach complex and abstract concepts in a short time, with examples or simple projects done in academic environments. Virtual Reality has demonstrated advantages applied to Education, providing immersive experiences and new ways of visualization and interaction. However, this technology has not been extensively explored in Software Engineering Education. In this sense, this paper aims to present a disruptive method of teaching and learning support on fundamentals in object orientation paradigm based on Immersive Learning, called OO Game VR. In addition, a preliminary study was performed with 6 subjects in order to identify usability problems. Despite problems found related to support learning, navigation and orientation, the natural expression of action and clear entry and exit points, the subjects were able to perform all the tasks, showing indications that the application has the potential to support teaching of OOP teaching through Immersive Learning. In future works, the usability problems will be fixed and specific methods will be applied for measuring influence immersion on learning outcomes.